Achievement of low-density lipoprotein cholesterol goals in 18 countries outside Western Europe: The International ChoLesterol management Practice Study (ICLPS). (July 2018) - Danchin, Nicolas; Almahmeed, Wael; Al-Rasadi, Khalid; Azuri, Joseph; Berrah, Abdelkrim; Cuneo, Carlos Alberto; Karpov, Yuri; Kaul, Upendra; Kayıkçıoğlu, Meral; Mitchenko, Olena; Ruiz, Alvaro J; Aguilar Salinas, Carlos A; et al.
Background: Little is known about the achievement of low density lipoprotein cholesterol (LDL-C) targets in patients at cardiovascular risk receiving stable lipid-lowering therapy (LLT) in countries outside Western Europe. Methods: This cross-sectional observational study was conducted in 452 centres (August 2015−August 2016) in 18 countries in Eastern Europe, Asia, Africa, the Middle East and Latin America. Patients ( n = 9049) treated for ≥3 months with any LLT and in whom an LDL-C measurement on stable LLT was available within the previous 12 months were included. Results: The mean±SD age was 60.2 ± 11.7 years, 55.0% of patients were men and the mean ± SD LDL-C value on LLT was 2.6 ± 1.3 mmol/L (101.0 ± 49.2 mg/dL). At enrolment, 97.9% of patients were receiving a statin (25.3% on high intensity treatment). Only 32.1% of the very high risk patients versus 51.9% of the high risk and 55.7% of the moderate risk patients achieved their LDL-C goals. On multivariable analysis, factors independently associated with not achieving LDL-C goals were no (versus lower dose) statin therapy, a higher (versus lower) dose of statin, statin intolerance, overweight and obesity, female sex, neurocognitive disorders, level of cardiovascular risk, LDL-C value unknown at diagnosis, high blood pressure and current smoking. Diabetes was associated with a lower risk of not achieving LDL-C goals. Conclusions: These observational data suggest that the achievement of LDL-C goals is suboptimal in selected countries outside Western Europe. Efforts are needed to improve the management of patients using combination therapy and/or more intensive LLTs.